Improving Standard Progressive Multiple Sequence Alignment by Using Multithreading Techniques - Mohamed, Eman M.; Mousa, Hamdy M.; keshk, Arabi E. (2018 14th International Computer Engineering Conference (ICENCO), 2018)
one of the most important goals in bioinformatics is the ideal alignment among three or even more sequences of Protein, DNA or RNA. The urgent problem in multiple sequence alignment (MSA) is to maximize accuracy and decreasing execution time. Progressive and Iterative techniques are most extensively used for solving MSA challenge. In this paper, we focus on progressive MSA of protein sequences. Progressive alignment with large-scale sequences will be time-consuming so parallelization is a key approach for decreasing the time execution. In this paper, we present a parallel implementation of progressive MSA based totally on java multithreading strategies. Experimental results have shown that the proposed approach is efficient for large-scale and shorter sequences.